Evaluation of early-age shrinkage cracking behavior of partially continuous reinforced concrete pavement using restrained ring test - Shujie Han; Xiao Zhang; Kaixiang Liu; Jiacheng Zhang; Jiahang Hao (Case Studies in Construction Materials)
Continuously reinforced concrete pavement (CRCP) has deficiencies such as high initial construction cost and irregular crack distribution. To address the shortcomings of CRCP, a rigid pavement structure called partially continuous reinforced concrete pavement (PCRCP) was proposed. Instead of reinforced concrete slabs in the field tests, concrete ring specimens with different reinforcement methods are designed based on the laboratory restrained ring test to comprehensively evaluate the early-age shrinkage cracking behavior of PCRCP. In addition, the effects of design parameters such as the partial continuous reinforcement length and partial continuous reinforcement spacing on the early-age shrinkage cracking behavior of PCRCP are investigated. Early-age cracking resistance of concrete is analyzed by residual tensile stress, cracking risk coefficient and stress development rate. The test results show that the arrangement of steel bars in the ring specimens can effectively limit the shrinkage of concrete, prolong the cracking age, and reduce the crack width. The concrete strain of ring specimens with active cracks is the smallest, indicating that active cracks can release the tensile stresses in the concrete due to limiting shrinkage. As the reinforcement ratio of the ring specimen increases, the longer the time for the first crack to occur, the crack width gradually decreases. The longer the partial continuous reinforcement length and the smaller the partial continuous reinforcement spacing, the better the cracking resistance of the concrete ring specimens. The location of active cracks has a greater effect on the early-age cracking behavior of PCRCP. This research can provide new insights into the evaluation of early-age cracking behavior of PCRCP and offer practical suggestions for its rational design.